RFID-based Object Detection During Video Production - Machado , Tiago; Moreno, Machado F. (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2016: Anais Estendidos do XXII Simpósio Brasileiro de Sistemas Multimídia e Web, 2016)
Recently, Digital TV Broadcasters have been concerned on how to adapt their workflow in order to embrace the production and delivery of interactive content. Due to the involved changes and costs, broadcasters could not yet fully explore the possibilities of interactivity that would enable an enhanced, pleasing user experience. It becomes essential for broadcasters to rely on new technologies that can lower the costs and assist the production of interactive content with a level of automation as high as possible. In this context, this work proposes an object detection method to be used during video capturing (offline or real-time) that delivers this information as a structured Object Timeline, which can be easily handled for the automated creation of interactive content and other applications. In order to lower the cost of object detection and making it faster and precise, this work evaluates the use of Radio Frequency Identification (RFID) as the relying tehnology for the proposed method.